INTEGRATION OF ISLAMIC VALUES IN ENGLISH SPEAKING CLASSES THROUGH CONTEXTUAL TEACHING AND LEARNING - Maya Astria (Universitas Negeri Islam Sumatera Utara, 2026)
This study aims to investigate the integration of Islamic values into English language learning, particularly in speaking classes, through the Contextual Teaching and Learning (CTL) approach. A qualitative approach was employed, using questionnaires and interviews as data collection techniques. The participants of this study consisted of English teachers and students. Questionnaire data were used to identify students' perceptions regarding the impact of integrating Islamic values into English learning, while interviews were conducted to explore students' experiences and teachers' perspectives in greater depth. The findings indicate that the integration of Islamic values into English language learning through the CTL approach helps students become more polite and contributes to character development. It also enhanced students’ self-confidence and strengthened their understanding of religious values. Furthermore, the use of the CTL approach, combined with Islamic topics that are relevant to students’ daily lives, facilitates meaningful learning and improves students’ comprehension of learning materials. This study concludes that integrating Islamic values through a contextual learning approach is an effective and relevant strategy that not only develops students’ speaking skills but also fosters their character and personality holistically, enabling them to apply these values in their everyday lives.